2010
DOI: 10.1159/000320326
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance Is Associated with Gestational Hypertension and Not with Preeclampsia: A Population-Based Screening Study

Abstract: Aims: To investigate the relationship between insulin resistance (IR) and subsequent gestational hypertension (GH) or preeclampsia (PE) in normoglycemic and in gestational diabetic pregnant women. Furthermore, we tested whether this association was independent of the prepregnancy body mass index (BMI). Methods: Each participant underwent a 75-gram oral glucose tolerance test (OGTT) according to World Health Organization recommendation criteria with determination of serum glucose and C-peptide concentrations. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In addition, 34.69% of the studies were conducted in the U.S. [22,24,25,31,33,34,[36][37][38]41,44,52,53,55,57,58,64], 14.2% in Australia [20,27,28,50,51,65,68], 28.5% in Asia [26,29,32,35,39,40,42,[46][47][48][49]60,63,66], and 22.4% in Europe [21,23,30,43,45,54,56,59,61,62,67].…”
Section: Literature Search Results and Quality Assessmentmentioning
confidence: 99%
“…In addition, 34.69% of the studies were conducted in the U.S. [22,24,25,31,33,34,[36][37][38]41,44,52,53,55,57,58,64], 14.2% in Australia [20,27,28,50,51,65,68], 28.5% in Asia [26,29,32,35,39,40,42,[46][47][48][49]60,63,66], and 22.4% in Europe [21,23,30,43,45,54,56,59,61,62,67].…”
Section: Literature Search Results and Quality Assessmentmentioning
confidence: 99%
“…Previous studies have shown similar comprehensive results. A cohort study including 2954 singleton pregnancies suggested that insulin resistance on an OGTT was associated with later development of gestational hypertension, but not preeclampsia, independent of maternal BMI [21]. Another study suggested that women who develop pregnancy-induced hypertension may be metabolically challenged at early stages of pregnancy with hyperinsulinism and insulin insensitivity [22].…”
Section: Discussionmentioning
confidence: 99%
“…FCGR is a measure of the amount of insulin secreted for a corresponding glucose level, and is considered a simplified index in the evaluation of insulin resistance compared with the euglycemic hyperinsulinemic clamp, which was regarded as the previous “gold standard”. In the study by Wang ( 28 ) and some other investigators ( 26 , 27 , 29 ), the fCGR index significantly increased in individuals with insulin resistance, and it was reported to present satisfactory specificity and sensitivity compared with euglycemic hyperinsulinemic clamps and HOMA indices. The results of our study therefore suggest that the level of insulin resistance in female MACS patients improves with the decline in autonomous cortisol secretion, and that this relationship only appears in premenopausal women with MACS and who manifest overt increases in autonomous cortisol secretion.…”
Section: Discussionmentioning
confidence: 92%